The prevalence of prediabetes in population of Polish men with late-onset hypogonadism. (September 2014) - Rabijewski, Michał; Papierska, Lucyna; Piątkiewicz, Paweł
Abstract Objective: Prediabetes patients are likely to develop type 2 diabetes (T2DM). Low testosterone is a risk factor for impaired glucose tolerance (IGT) in men. The aim of this study was to investigate the prevalence of prediabetes in population of Polish men with late-onset hypogonadism (LOH). Methods: This study was performed in 246 men with LOH and in 184 eugonadal control group. Prediabetes was diagnosed in patients with impaired fasting glucose (IFG), IGT or with HbA1c from 5.7 to 6.4%. Sex hormones and metabolic parameters were measured. Results: The mean TT concentration in the LOH group was 9.55 ± 1.5 nmol/l and 16.45 ± 1.8 nmol/l in the control group (p < 0.001). We observed negative relationships between cFT and HbA1c (r = −0.336; p < 0.005) and between TT and HbA1c (r = −0.366, p < 0.002), In the LOH group, prediabetes was diagnosed in 41.5% men. In the control group, prediabetes was diagnosed in 13% of patients. In the LOH group, TT and cFT levels were lower in prediabetic patients, when compared with normoglycemic patients and patients with IGT had lower TT levels than subgroups with IFG or elevated HbA1c. Conclusions: In a population of Polish men with LOH, we observed high prevalence of prediabetes and routine fasting glucose and glucose tolerance test should be performed in these patients.